Annular and Erosive Plaques on the Back of a Male Patient - Aline Garcia; Nicolas Poulalhon; Emmanuel Ribereau-Gayon (JAMA Dermatology, 2026)
A man in his 60s presents with a 30-year history of painful erythematous annular plaques on his back. What is your diagnosis?